Legal Implications of The Cancelation of Pataru Sere Sahatan (Engagement) in Mandailing Society, Pasar Binanga Village, Barumun Tengah Sub-District, Padang Lawas Regency, Indonesia) - Astria Is'a Anwi Siregar; Edy Ikhsan; Tengku Keizerina Devi (Wacana Journal of Social and Humanity Studies, 2020)
Engagement is an initial action before a marriage. In jurisprudence, it is considered as a bond in which, if it is canceled unilaterally it will cause legal implications such as the injured party. The research used a juridical empirical method. The nature of the research was descriptive analytic. The result of the research shows that in the unwritten Mandailing customary law, the process of engagement is done orally based on their belief, starting from adat procession. The procedure of engagement in the Mandailing community in the post-jurisprudence is that the series of the engagement is in the written form to make it authentic evidence to be used when there is a dispute in the cancelation of engagement. The Mandailing customary law at Pasar Binanga Village does not recognize default complaint in litigation when one of the parties breaks it as it is stipulated in Article 1243 and Article 1365 of the Civil Code. However, the Supreme Court’s Ruling No. 396K/Sip/1958 and No. 68K/Pdt/2009 states that the cancelation of engagement by one of the parties in customary law is considered a default and illegal based on the consideration that the engagement is a pledge between the future groom’s side and the future bride’s side which has to be made by good faith.